Climate‐related range shifts in Arctic‐breeding shorebirds. Issue 2 (7th February 2023) - Anderson, Christine M.; Fahrig, Lenore; Rausch, Jennie; Martin, Jean‐Louis; Daufresne, Tanguy; Smith, Paul A.
Abstract: Aim: To test whether the occupancy of shorebirds has changed in the eastern Canadian Arctic, and whether these changes could indicate that shorebird distributions are shifting in response to long‐term climate change. Location: Foxe Basin and Rasmussen Lowlands, Nunavut, Canada. Methods: We used a unique set of observations, made 25 years apart, using general linear models to test if there was a relationship between changes in shorebird species' occupancy and their species temperature Index, a simple version of a species climate envelope. Results: Changes in occupancy and density varied widely across species, with some increasing and some decreasing. This is despite that overall population trends are known to be negative for all of these species based on surveys during migration. The changes in occupancy that we observed were positively related to the species temperature index, such that the warmer‐breeding species appear to be moving into these regions, while colder‐breeding species appear to be shifting out of the regions, likely northward. Main Conclusions: Our results suggest that we should be concerned about declining breeding habitat availability for bird species whose current breeding ranges are centered on higher and colder latitudes. Abstract : We used a unique set of observations, made 25 years apart, using general linear models to test if there was a relationship between changes in shorebird species' occupancy and their species temperature index, a simple version of a species' climate envelope. The changes in occupancy that we observed were positively related to the species temperature index, such that the warmer‐breeding species appear to be moving into these regions, while colder‐breeding species appear to be shifting out of the regions, likely northward. Our results suggest that we should be concerned about declining breeding habitat availability for bird species whose current breeding ranges are centered on higher and colder latitudes.